ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI TINGKAT PARTISIPASI ANGKATAN KERJA DI PROVINSI DKI JAKARTA - Ayuni Mila Ningrum; Lisa Amelia; Deris Desmawan (Profit: Jurnal Manajemen, Bisnis dan Akuntansi, 2022)
This study aims to identify the independent variables that affect the level of labor force participation in the DKI Jakarta area. There are four independent variables studied, namely Gross Domestic Product (X1) or commonly known as GRDP, then Provincial Minimum Wage (X2), then there is Domestic Investment (X3), and the last variable is Foreign Investment (X4). Meanwhile, the dependent variable in this study is the Labor Force Participation Rate (Y). The current study applies a data panel that combines cross-sectional and time-series data. The data analysis technique applied in this study is multiple linear analysis using the Eviews10 program. After conducting the test, the researcher found that there was a significant correlation between the alpha GRDP and PMA variables, which was about 5% higher than the LFPR. On the other hand, the Provincial Minimum Wage and Domestic Investment are two factors that have little influence on the determinants of the level of labor force participation.